AL-MAKHTŪTĀT DAN AL-MAKHFŪẒĀT - Ahmad Fauzi; Abdul Latif; Khoirul Anam (LPPM IAI Hasanuddin Pare-Kediri, 2026)
The makhtūṭāt and makhfūẓāt of hadith are crucial primary sources in both classical and contemporary hadith studies. The existence of hadith manuscripts scattered across libraries in the Islamic and Western world holds a wealth of scholarship that has not yet been fully studied in depth. Many of these manuscripts contain variant texts, sanad (transcribers), and scholarly notes that have the potential to enrich understanding of the transmission, codification, and authenticity of hadith. However, the lack of systematic study of the makhtūṭāt and makhfūẓāt of hadith has resulted in these sources being underutilized in modern hadith studies. This study aims to examine the concepts of makhtūṭāt and makhfūẓāt of hadith, identify their role in the development of hadith science, and analyze their contribution to the study of sanad and matan criticism. The research method used was library research, examining written sources in the form of hadith manuscripts, manuscript catalogs, books on hadith, and related academic literature. Data were analyzed using a descriptive-analytical and historical approach to understand the position and significance of hadith manuscripts within the Islamic scholarly tradition. This research is expected to provide theoretical contributions to the development of manuscript-based hadith studies and encourage the preservation and further study of Islamic intellectual heritage.